BUDAYA KERJA EWUH PAKEWUH DI KALANGAN PEGAWAI NEGERI SIPIL ETNIK JAWA (STUDI PADA KABUPATEN PASAMAN BARAT, PROVINSI SUMATERA BARAT) - Frinaldi, Aldri; Ali Embi, Muhamad (Humanus, 2014)
This research aims to analyze the influence of ethnic work culture ‘ewuh pakewuh’ of civil servant working in the West Pasaman regency. Ethnic work culture ‘ewuh pakewuh’ is someone’s behavior of worrying his/her attitude or remark wiil offend other people. This research used qualitative approach. Informants are selected using purposive sampling of civil servants from Javanese ethnic group who work in West Pasaman administration. The sample are also selected using snowball and convenience/accidental method. The research is conducted in local inspectorate, plantation agency, civil servant agencies, education and training agency, and local secretariat. Informants consist of 2 echelon III officials, 2 echelon IV and 8 staff. Data is interpreted using thick description method; so that the cultural significance of this work ethic can be explored more intensely in order to elaborate deeply the ewuh pakewuh work culture beyond what is visible. The results obtained indicate that the ethnic work culture ewuh pakewuh have positive and negative sides. The positive side shows high appreciation for higher authority, and an effort to respect and implement sincerely the policies made by the authority. However the ewuh pakewuh ethnic work culture discourages the staff to give suggestions and opinions, causing uncritical (nrimo) work culture. A change is needed to encourage them implement less the ewuh pakewuh that leads to ethnic work culture in order to create creative and innovative work culture. This change has to be started by the leaders and staff to establish an egalitarian culture in the working environment of the local goverment agencies.Key words: Ethnic Work Culture, Ewuh Pakewuh, Civil Servants